Краскові роговики Ташлицького комплексу та проблема залізних в археології - Петрунь, В.Ф. (Материалы по археологии Северного Причерноморья, 2015)
The paper gives the results of geological and petrologic investigations of rock samples from Tashlik site (Sabatinovskaja culture of the Late Bronze Age). Several issues are raised by the author: 1) the problem of origin of ferric-containing «red» ore of Krivorozhskiy type; 2) the range of use of the latter (in metallurgy and as painting device) since the Eneolithic; 3) the problems of specific terminology usage in relation to similar geological stuff; 4) the need for qualified archaeological and petrologic case-analysis.